Sleep duration, risk of obesity, and parental perceptions of residential neighborhood environments in 6–9 years‐old children. Issue 4 (19th August 2021) - Machado‐Rodrigues, Aristides M.; Rodrigues, Daniela; Gama, Augusta; Nogueira, Helena; Mascarenhas, Luís P.; Padez, Cristina
Abstract: Objectives: The present study aimed to analyze the association between healthy sleep duration of children and the parental perception of the social/built environment. Methods: A cross‐sectional study was done and a sample of 8273 children (4183 females) aged 6–9 years was observed. Height (cm) and weight (Kg) were measured, and the body mass index (BMI) was calculated. Participants were classified as normal weight or overweight/obese. Sleep habits, sedentary behaviors (i.e., TV viewing) and environmental variables were assessed by questionnaire. Logistic regressions were used, with adjustments for age, sex, BMI, and sedentary time. Results: Children whose parents reported a positive perception of the built environment in the residential area were 1.21 times more likely to have regular sleep habits during weekdays. Furthermore, children whose parents reported a negative perception of the social environment and safety were 81% more likely to have irregular sleep habits during the weekdays. Conclusions: The present study revealed a positive association between regular sleep during the weekdays and the parental perception of the social/built environment (land use and urban design).